AN ILLUMINATIVE EVALUATION OF ARABIC LANGUAGE AND ISLAMIC VALUES EDUCATION (ALIVE) PROGRAM IN THE PHILIPPINES: THE CASE OF FIVE (5) ELEMENTARY SCHOOLS IN THREE CITIES - Ma. Arsenia C. Gomez, - (2019)
The study examined the Arabic Language and Islamic Values Education (ALIVE) Program in the Philippines through the lens of illuminative evaluation. The topic was born out of the researcher's interest in Islam and its believers. In 2005, in its desire to promote better relations between the Philippine government and Muslim Filipinos, the Philippine government through the Department of Education launched ALIVE. Almost 14 years in the public school system, the curriculum/program has been studied and evaluated but by a limited number of individuals and institutions only. Moreover, evaluations of ALIVE often looked at the actual conduct of the program/curriculum, usually focused on the instructional system such as teachers and the facilities. The researcher felt that this focus was not broad enough to shed light on the actual implementation of the program. Through illuminative evaluation approach which considers both the instructional system and the learning milieu as the main elements that can affect a program, the researcher found a means to better study the program. The study involved five (5) public elementary schools located in the cities of Manila, Sta. Rosa, and Baguio. Data gathering in the form of several observations and interviews were conducted in November 2017-February 2018. In the study, it was established that the success or failure of ALIVE's implementation lies primarily on the dedication and effectiveness of the ALIVE Ustadz, leadership of the principal, and the mobilized community support given to the program. The last two factors were significantly influenced by their knowledge and understanding of Islam and Muslims which in turn affect their views on the program. Almost 15 years as a program in public schools, ALIVE is still replete with challenges from the instructional system and learning milieu that can be remedied or solved if the school leadership and the DepEd wish to.